2013
DOI: 10.2967/jnumed.112.109652
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Myocardial Perfusion Reserve Using Dynamic SPECT Imaging in Humans: A Feasibility Study

Abstract: Myocardial perfusion imaging (MPI) is well established in the diagnosis and workup of patients with known or suspected coronary artery disease (CAD); however, it can underestimate the extent of obstructive CAD. Quantification of myocardial perfusion reserve with PET can assist in the diagnosis of multivessel CAD. We evaluated the feasibility of dynamic tomographic SPECT imaging and quantification of a retention index to describe global and regional myocardial perfusion reserve using a dedicated solid-state car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
129
0
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(149 citation statements)
references
References 34 publications
12
129
0
8
Order By: Relevance
“…It is caused by linear dependence of [ 15 O]H 2 O extraction fraction on myocardial flow rate as well as by higher resolution power of positron emission tomography scanners. Data obtained in our study agree with the results of other research groups who showed principal feasibility of myocardial flow reserve assessment by the methods of dynamic SPECT [4,6,7] or planar scintigraphy [2] with high diagnostic accuracy values.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…It is caused by linear dependence of [ 15 O]H 2 O extraction fraction on myocardial flow rate as well as by higher resolution power of positron emission tomography scanners. Data obtained in our study agree with the results of other research groups who showed principal feasibility of myocardial flow reserve assessment by the methods of dynamic SPECT [4,6,7] or planar scintigraphy [2] with high diagnostic accuracy values.…”
Section: Resultssupporting
confidence: 82%
“…Literature describes this phenomenon by term "balanced ischemia" where a uniform decrease in an indicator accumulation is observed over the entire left ventricular (LV) myocardium [5,6]. One of the ways to diagnose balanced ischemia of the myocardium in multivessel coronary artery disease consists in an assessment of myocardial flow reserve [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of semiconductor detector technology using synthetic crystals composed of CZT undeniably constituted a revolutionary milestone in technical innovation for nuclear MPI, offering a variety of interesting new possibilities ranging from dynamic SPECT imaging for non-invasive quantitation of myocardial blood flow, 8 over respiratory triggering, 9 to low isotope dose SPECT with significantly reduced ionizing radiation exposure. 10 However, particularly the strive for a further reduction in radiation dose exposure will in turn inevitably again lead to a future increase in acquisition times because with the current CZT system sensitivity very short acquisition times of only 2 or 3 min may not yield sufficient count statistics if the isotope dose is substantially reduced.…”
mentioning
confidence: 99%
“…17 The problem caused by qualitative imaging is uncertain. Non-regional markers of ischemia such as hemodynamic and ECG changes, post-stress LV stunning, transient RV prominence, and lung activity often flag when qualitative SPECT may be underestimating ischemia.…”
Section: How Do the Imaging Characteristics Of 82 Rb Compare With Thomentioning
confidence: 99%